Impact and effectiveness of risk mitigation strategies on the insurability of nanomaterial production: evidences from industrial case studies. (24th March 2015) - Bergamaschi, Enrico; Murphy, Finbarr; Poland, Craig A.; Mullins, Martin; Costa, Anna L.; McAlea, Eamonn; Tran, Lang; Tofail, Syed A. M.
Abstract : Workers involved in producing nanomaterials or using nanomaterials in manufacturing plants are likely to have earlier and higher exposure to manufactured/engineered nanomaterials (ENM) than the general population. This is because both the volume handled and the probability of the effluence of 'free' nanoparticles from the handled volume are much higher during a production process than at any other stage in the lifecycle of nanomaterials and nanotechnology‐enabled products. Risk assessment (RA) techniques using control banding (CB) as a framework for risk transfer represents a robust theory but further progress on implementing the model is required so that risk can be transferred to insurance companies. Following a review of RA in general and hazard measurement in particular, we subject a Structural Alert Scheme methodology to three industrial case studies using ZrO2, TiO2, and multi‐walled carbon nanotubes (MWCNT). The materials are tested in a pristine state and in a remediated (coated) state, and the respective emission and hazard rates are tested alongside the material performance as originally designed. To our knowledge, this is the first such implementation of a CB RA in conjunction with an ENM performance test and offers both manufacturers and underwriters an insight into future applications. WIREs Nanomed Nanobiotechnol 2015, 7:839–855. doi: 10.1002/wnan.1340 This article is categorized under: Toxicology and Regulatory Issues in Nanomedicine > Regulatory and Policy Issues in Nanomedicine